Contribution of trees to carbon stocks in urban–rural ecosystems: Taxonomic, phylogenetic, and functional diversity in response to bioclimatic and geographic factors (Scientia Agropecuaria, 2025)
Tree diversity plays a key role in mitigating climate change and enhancing ecosystem resilience. This study evaluated the contribution of trees across three habitats within the urban–rural gradient of Sucre, Bolivia: urban (UF), native (NF), and exotic (EF). Carbon sequestration, as well as taxonomic (TD), phylogenetic (PD), and functional (FD) diversity, were analyzed in relation to bioclimatic (temperature and precipitation) and geographic (altitude) factors. The methodology included the recording of botanical and ecological traits, along with the measurement of dendrometric classes (DBH ≥ 10 cm) in 12 temporary circular plots per habitat. Results showed higher carbon stocks in the urban forest (268.36 ± 2.76 MgC/ha), followed by the exotic (159.53 ± 0.86 MgC/ha) and the native forest (39.64 ± 0.41 MgC/ha). A total of 31 species from 19 families were identified, with marked evolutionary divergence between Pinaceae and Cupressaceae compared to Fabaceae. The urban habitat presented the highest taxonomic diversity (~51.6%), the highest phylogenetic diversity (~72%), and the greatest carbon fixation (~42%). These findings highlight the fundamental role of tree diversity in carbon sequestration, biodiversity conservation, and landscape connectivity, emphasizing the need to integrate it into sustainable urban–rural planning through adaptation and mitigation strategies that strengthen ecological resilience and ecosystem services in the urban–rural ecosystem of Sucre.
Keywords: evolutionary relationships; species composition; sub-Andean ecosystem; tree richness; traits functions